The contribution of human-induced climate change to the drought of 2014 in the southern Levant region - Bergaoui, K; Mitchell, D; Zaabould, R; McDonnell, R; Otto, F; Allen, M (American Meteorological Society, 2015)
A combined modeling and observational study suggests that the persistent rainfall deficit during the 2014 rainy season in southern Levant was made more likely due to anthropogenic climate change.